Fighting the people's war the British and Commonwealth armies and the Second World War - Fennell, Jonathan 1979 (Armies of the Second World War, 2018)
"In citizen armies, it matters enormously that soldiers should, as Oliver Cromwell put it, know what they fight for and love what they know; the fundamentals of victory or defeat 'often have to be sought far from the battlefield, in political, social, and economic factors'. This study of the British and Commonwealth armies in the Second World War, a fighting force made up predominantly of contingents from Britain, Australia, Canada, India, New Zealand and South Africa, explores not only the material culture and history of great armies in a world war, but also the political, social, and economic factors that influenced their behaviour and experience in the period running up to and during the largest conflagration of the twentieth century"--